Effects of berberine of L- and T-type calcium channels in guinea pig ventricular myocytes - Xu Shang-Zhong; Zhang Yi; Ren Jian-Ying; Zhou Zhao-Nian (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of berberine (Ber) on L-(ICa,L) and T-type (ICa,T) channels in isolated guinea pig ventricular myocytes. METHODS: Using whole cell patch-clamp recording technique. RESULTS: Ber 10, 30 mumol.L-1 inhibited the ICa, L from 1400 +/- 247 pA to 978 +/- 204 pA (n = 5 cells of 5 guinea pigs, P < 0.05), and to 664 +/- 179 pA (n = 5, P < 0.01), respectively. The inhibitory effect was concentration-dependent and non-frequency-dependent. The peak value of ICa,L in the current-voltage relationship was decreased. Ber affected the inactivation kinetics of ICa,L. The half activation potential (V0.5) was shifted from -27.8 mV to -34.2 mV and the slope factor (kappa) was changed from 9.22 into 13.03. Ber did not affect the activation kinetics. Ber 10 and 30 mumol.L-1 also inhibited ICa,T (from 154 +/- 80 pA to 101 +/- 78 pA, and to 48 +/- 45 pA, n = 8 cells of 5 guinea pigs, P < 0.05). CONCLUSION: Ber possessed blocking effects on both L- and T-type calcium channels.